Phanerozoic amalgamation of the Alxa Block and North China Craton: Evidence from Paleozoic granitoids, U-Pb geochronology and Sr-Nd-Pb-Hf-O isotope geochemistry - Dan, W.; Li, X.; Wang, Q.; Wang, Xuan-Ce; Wyman, D.; Liu, Y. (Elsevier BV, 2016)
The North China Craton (NCC) has been considered to be part of the supercontinent Columbia. The nature of the NCC western boundary, however, remains strongly disputed. A key question in this regard is whether or not the Alxa Block is a part of the NCC. It is located in the vicinity of the inferred boundary, and therefore could potentially resolve the issue of the NCC's relationship to the Columbia supercontinent. Some previous studies based on the Alxa Block's geological evolution and detrital zircon ages suggested that it is likely not a part of the NCC. The lack of evidence from key igneous rock units, however, requires further constraints on the tectonic affinity of the western NCC and Alxa Block and on the timing of their amalgamation.The North China Craton (NCC) has been considered to be part of the supercontinent Columbia. The nature of the NCC western boundary, however, remains strongly disputed. A key question in this regard is whether or not the Alxa Block is a part of the NCC. It is located in the vicinity of the inferred boundary, and therefore could potentially resolve the issue of the NCC's relationship to the Columbia supercontinent. Some previous studies based on the Alxa Block's geological evolution and detrital zircon ages suggested that it is likely not a part of the NCC. The lack of evidence from key igneous rock units, however, requires further constraints on the tectonic affinity of the western NCC and Alxa Block and on the timing of their amalgamation.The differences in whole rock Nd model ages and Pb isotope compositions of the Paleoproterozoic–Permian rocks in either side of the west fault of the Bayanwulashan–Diebusige complexes suggest that the Alxa Block is not a part of the NCC, and that the western boundary of the NCC is probably located on this fault. Furthermore, the linear distribution of the Early Paleozoic–Early Carboniferous granitoids, the high zircon δ18O values of the Late Silurian quartz diorites, the Early Devonian metamorphism and the foreland basin system formed during the collision between the Alxa Block and the NCC indicate that a Paleozoic cryptic suture zone likely existed in this area and records the amalgamation of the Alxa Block and North China Craton. Together with detrital zircon data, the initial collision was considered to have possibly occurred in Late Ordovician.